Modelling of the Traffic Flow Basic Characteristics at the Road Network Selected Section - Alica Kalašová; Simona Skřivánek Kubíková; Veronika Harantová (Communications - Scientific letters of the University of Zilina, 2021)
Elimination of connection between an increase in transport and economic growth has been the main aim of the transport policy of the EU for a few years and it has not been accomplished yet. Transportation causes considerable external costs that have concrete originators but are not paid by them. The biggest external costs are connected with emissions, noise, accidents and congestions. In this contribution, the problem of congestions, which currently bother drivers in EU was analysed, together with possibilities for their solving, since the congestions' reduction is one of the priorities of the EU’s transport policy. The task was to observe a relation between the basic traffic flow characteristics on the specific section of the road no. I/65 and to identify effects on traffic in general, as well as to specify reasons and conditions within the traffic congestions that occurred. These results are a basis for the theoretical proposal of possible solutions of the issue.